Estudo da cadeia de transporte de elétrons fotossintético em folhas destacadas de ervilha - Farias, Márcio Espinosa de (2014)
Photosynthesis plays a fundamental role in the processes of growth and development of plants. It occurs in the chloroplasts of leaf mesophyll cells and consists of two steps, a photochemical phase that converts light energy into chemical energy, and other biochemical phase, which uses the energy of the first step for fixing CO2. The study aimed to evaluate, in detached leaves of pea (Pisum sativum L.), the behavior of the electron transport chain in the presence of inhibitors of specific points. The plants were grown in a greenhouse. Two to four weeks after sowing, when the leaves had become fully expanded, they were detached and the petioles were immersed in solutions containing 0, 25, 50, 100, 250, and 500 μM of DCMU, atrazine, DBMIB and methyl viologen. To DCMU, atrazine and methyl viologen the leaves remained for 2 h in contact with the solutions, to DBMIB was 5h. Measurements of transient fluorescence of chlorophyll, delayed fluorescence and modulated reflection at 820nm were made using M-PEA fluorometer. The leaves were dark adapted for 30 minutes, before a saturating pulse emission, and the fluorescence intensities were measured for 60 seconds. Pea leaves treated with 500 μM concentration of DCMU and atrazine showed to be sensitive to this dose of inhibitors, in analyzing the results of transient fluorescence, delayed fluorescence and modulated reflection at 820 nm. The leaves treated with 500 μM of methyl viologen showed differences in parameters related to the mechanism of action of the inhibitor.The same concentration used to DBMIB, had no significant difference in many results compared to the control, only in those involved in the reduction of end acceptors of photosystem I. Therefore, a detailed analysis of the transient fluorescence, delayed fluorescence and modulated reflection at 820nm, allows us to collect and correlate a series of information about the whole electron transport chain.